PROBLEMS OF OWNERSHIP IN ECONOMICS - Zalesko, Marian (Ekonomia i Prawo. Economics and Law, 2007)
Economists define ownership as a foundation of every social relations. Institutional economics deals with ownership, especially property rights economics. To expose ownership affairs, institutional economists seek to fill the gap existing in mainstream economics, which undervalues the significance of institutions through many years. Nowadays, in economic literature we often can find the argument, that the institutional system with ownership rights, as a most important type of institutions is the basis of economic development.